Long-term outcomes after catheter-based renal artery denervation for resistant hypertension: final follow-up of the randomised SYMPLICITY HTN-3 Trial. Issue 10361 (22nd October 2022) - Bhatt, Deepak L; Vaduganathan, Muthiah; Kandzari, David E; Leon, Martin B; Rocha-Singh, Krishna; Townsend, Raymond R; Katzen, Barry T; Oparil, Suzanne; Brar, Sandeep; DeBruin, Vanessa; Fahy, Martin; Bakris, George L; et al.
Summary: Background: The SYMPLICITY HTN-3 (Renal Denervation in Patients With Uncontrolled Hypertension) trial showed the safety but not efficacy of the Symplicity system (Medtronic, Santa Rosa, CA, USA) at 6 months follow-up in patients with treatment-resistant hypertension. This final report presents the 36-month follow-up results. Methods: SYMPLICITY HTN-3 was a single-blind, multicentre, sham-controlled, randomised clinical trial, done in 88 centres in the USA. Adults aged 18–80 years, with treatment-resistant hypertension on stable, maximally tolerated doses of three or more drugs including a diuretic, who had a seated office systolic blood pressure of 160 mm Hg or more and 24 h ambulatory systolic blood pressure of 135 mm Hg or more were randomly assigned (2:1) to receive renal artery denervation using the single electrode (Flex) catheter or a sham control. The original primary endpoint was the change in office systolic blood pressure from baseline to 6 months for the renal artery denervation group compared with the sham control group. Patients were unmasked after the primary endpoint assessment at 6 months, at which point eligible patients in the sham control group who met the inclusion criteria (office blood pressure ≥160 mm Hg, 24 h ambulatory systolic blood pressure ≥135 mm Hg, and still prescribed three or more antihypertensive medications) could cross over to receive renal artery denervation. Changes in blood pressure up to 36 months were analysed in patients in the original renal artery denervation group and sham control group, including those who underwent renal artery denervation after 6 months (crossover group) and those who did not (non-crossover group). For comparisons between the renal artery denervation and sham control groups, follow-up blood pressure values were imputed for patients in the crossover group using their most recent pre-crossover masked blood pressure value. We report long-term blood pressure changes in renal artery denervation and sham control groups, and investigate blood pressure control in both groups using time in therapeutic blood pressure range analysis. The primary safety endpoint was the incidence of all-cause mortality, end stage renal disease, significant embolic event, renal artery perforation or dissection requiring intervention, vascular complications, hospitalisation for hypertensive crisis unrelated to non-adherence to medications, or new renal artery stenosis of more than 70% within 6 months. The trial is registered with ClinicalTrials.gov, NCT01418261 . Findings: From Sep 29, 2011, to May 6, 2013, 1442 patients were screened, of whom 535 (37%; 210 [39%] women and 325 [61%] men; mean age 57·9 years [SD 10·7]) were randomly assigned: 364 (68%) patients received renal artery denervation (mean age 57·9 years [10·4]) and 171 (32%) received the sham control (mean age 56·2 years [11·2]). 36-month follow-up data were available for 219 patients (original renal artery denervation group), 63 patients (crossover group), and 33 patients (non-crossover group). At 36 months, the change in office systolic blood pressure was –26·4 mm Hg (SD 25·9) in the renal artery denervation group and –5·7 mm Hg (24·4) in the sham control group (adjusted treatment difference –22·1 mm Hg [95% CI –27·2 to –17·0]; p≤0·0001). The change in 24 h ambulatory systolic blood pressure at 36 months was –15·6 mm Hg (SD 20·8) in the renal artery denervation group and –0·3 mm Hg (15·1) in the sham control group (adjusted treatment difference –16·5 mm Hg [95% CI –20·5 to –12·5]; p≤0·0001). Without imputation, the renal artery denervation group spent a significantly longer time in therapeutic blood pressure range (ie, better blood pressure control) than patients in the sham control group (18% [SD 25·0] for the renal artery denervation group vs 9% [SD 18·8] for the sham control group; p≤0·0001) despite a similar medication burden, with consistent and significant results with imputation. Rates of adverse events were similar across treatment groups, with no evidence of late-emerging complications from renal artery denervation. The rate of the composite safety endpoint to 48 months, including all-cause death, new-onset end-stage renal disease, significant embolic event resulting in end-organ damage, vascular complication, renal artery re-intervention, and hypertensive emergency was 15% (54 of 352 patients) for the renal artery denervation group, 14% (13 of 96 patients) for the crossover group, and 14% (10 of 69 patients) for the non-crossover group. Interpretation: This final report of the SYMPLICITY HTN-3 trial adds to the totality of evidence supporting the safety of renal artery denervation to 36 months after the procedure. From 12 months to 36 months after the procedure, patients who were originally randomly assigned to receive renal artery denervation had larger reductions in blood pressure and better blood pressure control compared with patients who received sham control. Funding: Medtronic